The Volatility and Growth Trend of Field Production Mechanization Level in China - A Positive Analysis Based on Hodrick-Prescott Method - X., Huang Y.; H., Yang X.; S., Huang; R., Zhu; Z., Zhang (IntechOpen, 2011)
None